Pelembagaan Collaborative Governance dalam Penguatan Mutu Layanan Administrasi Madrasah - Afifah Khairunnisa; Wenny Agustina; Okke Rosmaladewi (Kariman: Jurnal Pendidikan Keislaman, 2026)
This study analyzes the institutionalization of collaborative governance in strengthening administrative service quality in a madrasah. Administrative services support school governance, information transparency, academic document management, and public trust. This study used a qualitative case study method at MTs Al Hasan Karawang. Data were collected through in-depth interviews, observation, and documentation involving 11 informants, including the principal, teachers, administrative staff, school committee members, parents, and students. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña through data condensation, data display, and conclusion drawing. The findings show that administrative service improvement has involved various stakeholders through communication, coordination, document management, information sharing, and complaint handling. However, the collaboration remains largely informal and has not been fully supported by integrated digital systems, clear service standards, and regular data-based evaluation. This study concludes that administrative service quality can be strengthened through facilitative leadership, clear stakeholder role division, gradual administrative digitalization, administrative staff capacity building, and data-based service evaluation.